Special Issue: Age and Growth of Chondrichthyan Fishes: New Methods, Techniques and Analysis - Carlson, John K.; Goldman, Kenneth J. (Developments in Environmental Biology of Fishes, 2006)
Shark conservation and management is often hindered by a lack of basic biological information for most species. An understanding of the age structure and growth dynamics of a population is important for effective conservation and management because this information is often utilized for determination of natural mortality and longevity. Ultimately age and growth information is used for calculation of vital rates in population models. Over the last few years there have been advances in the quantitative study of age and growth of chondrichthyan fishes. Novel approaches to ageing of various chondrichthyan fishes continue to arise. This volume is a collection of papers on several of these topics that include new hard parts (e.g. caudal thorns) for assessments of age, new techniques for validation (e.g. bomb radiocarbon) and reexaminations of previous age and growth models. This volume also contains papers on the importance of assessing the precision and accuracy of statistical formulas, analyses, and models that are used in age and growth studies. There is currently a great deal of research being conducted, some of which is truly "pushing the envelope," in attempts to assess the life history parameters of numerous chondrichthyan fishes.